Varied distributions of late gadolinium enhancement found among patients meeting cardiovascular magnetic resonance criteria for isolated left ventricular non-compaction - Wan, Junyi (BioMed Central, 2013)
BACKGROUND: Late gadolinium enhancement (LGE) is identified frequently in LVNC. However, the features of this findings are limited. The purpose of the present study was to describe the frequency and distribution of LGE in patients meeting criteria for left ventricular non-compaction (LVNC), as assessed by cardiovascular magnetic resonance (CMR). METHODS: Forty-seven patients (37 males and 10 females; mean age, 39 ± 18 years) considered to meet standard CMR criteria for LVNC were studied. The LGE images were obtained 15 ± 5 min after the injection of 0.2 mmol/kg of gadolinium-DTPA using an inversion-recovery sequence, and analyzed using a 17-segment model. RESULTS: Mean number of non-compacted segments per patient was 7.4 ± 2.5 and the NC:C was 3.2 ± 0.7. Non-compaction was most commonly noted in the apical segments in all patients. LGE was present in 19 of the 47 patients (40%), and most often located in the ventricular septum. The distribution of LGE was subendocardial (n = 5; 6%), mid-myocardial (n = 61; 68%), subepicardial (n = 10; 11%), and transmural (n = 14; 15%) in total of 90 LGE (+) segments. CONCLUSIONS: In patients considered to meet criteria for LVNC, LGE distributions visible were strikingly heterogeneous with appearances potentially attributable to three or more distinct cardiomyopathic processes. This may be in keeping with previous suggestions that the criteria may be of low specificity. Further work is needed to determine whether conditions such as dilated cardiomyopathy, previous myocardidtis or ischaemic heart disease increase the apparent depth of non-compact relative to compact myocardium.